1983
DOI: 10.1111/j.1432-1033.1983.tb07429.x
|View full text |Cite
|
Sign up to set email alerts
|

The Refined Structure of the Selenoenzyme Glutathione Peroxidase at 0.2‐nm Resolution

Abstract: The crystal structure of bovine erythrocyte glutathione peroxidase has been refined by a combined procedure of restrained crystallographic refinement and energy minimization at 0.20 nm resolution. The final R value at this resolution is 0.178. The r.m.s. deviation of main-chain atoms of the two independently refined monomers is 0.019 nm. The structure at 0.28 nm resolution, which has been determined by multiple isomorphous replacement, served as a starting model.The refined model allowed a detailed survey of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
458
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 657 publications
(480 citation statements)
references
References 39 publications
(28 reference statements)
15
458
1
6
Order By: Relevance
“…4). This loop does not originate from the thioredoxin domain, but the ␤3/␣3 turn is also exploited in other thioredoxin-related proteins for non-related inserts of varying size and structure (14,15). In these proteins it has been suggested that the insertion may play a role in substrate binding (14).…”
Section: Most Wind Mutants Display Normal Expression and Dimerizationmentioning
confidence: 99%
“…4). This loop does not originate from the thioredoxin domain, but the ␤3/␣3 turn is also exploited in other thioredoxin-related proteins for non-related inserts of varying size and structure (14,15). In these proteins it has been suggested that the insertion may play a role in substrate binding (14).…”
Section: Most Wind Mutants Display Normal Expression and Dimerizationmentioning
confidence: 99%
“…Structural models of GPx4 have been generated (Aumann et al, 1997;Mauri et al, 2003) based on the X-ray coordinates of other GPx isoforms (Epp et al, 1983;Ren et al, 1997). Although the degree of amino acid conservation among GPx isoforms is rather low, these models served in the past as suitable tools to predict target amino acids for site-directed mutagenesis to impede the catalytic activity (Maiorino et al, 1995(Maiorino et al, , 1998.…”
Section: Molecular Enzymology and Structural Aspects Of Gpx4mentioning
confidence: 99%
“…Selenium proved to be present in this enzyme as a selenocysteine residue (Forstrom et al, 1978, Wendel et al, 1978 that is integrated into the amino acid chain (Günzler et al, 1984). The selenocysteine residue in GPx is responsible for the catalytic efficiency, as demonstrated by site-directed mutagenesis (Rocher et al, 1992), and the X-ray analysis performed by Epp et al (1983) enabled a detailed understanding of the catalytic mechanism (Aumann et al, 1997; see also Figure 1A). …”
Section: Introduction: Some Historical Landmarksmentioning
confidence: 99%